2022
DOI: 10.3389/fmars.2022.980705
|View full text |Cite
|
Sign up to set email alerts
|

A growing crisis for One Health: Impacts of plastic pollution across layers of biological function

Abstract: The global accumulation of plastic waste has reached crisis levels. The diverse and multilayered impacts of plastic on biological health prompts an evaluation of these effects from a One Health perspective, through which the complexity of these processes can be integrated and more clearly understood. Plastic particles ranging from nanometers to meters in size are found throughout every ecosystem on Earth, from the deepest marine trenches to the highest mountains. Plastic waste affects all layers of biological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 163 publications
0
11
0
Order By: Relevance
“…Besides agriculture and ecosystems monitoring, environmental clean-up constitutes a pressing environmental issue [43] that would require a high degree of efficiency that can likely only be realized with some degree of automation. An example for this would be the removal of plastic waste from land, water ways of all sizes, as well the oceans.…”
Section: Importance Of Autonomy In Natural Environmentsmentioning
confidence: 99%
“…Besides agriculture and ecosystems monitoring, environmental clean-up constitutes a pressing environmental issue [43] that would require a high degree of efficiency that can likely only be realized with some degree of automation. An example for this would be the removal of plastic waste from land, water ways of all sizes, as well the oceans.…”
Section: Importance Of Autonomy In Natural Environmentsmentioning
confidence: 99%
“…Studies have shown that rising consumption of plastic can be linked to markets, governance, regulatory systems, changing demographic patterns, and ideologies of modernity and what constitutes a good standard of living (Johnson & Bell, 2023). Environmental justice perspectives can further be incorporated to go beyond average demographic changes and GDP to give insights into uneven distribution of harm from exposure to MPW, such as differences between high‐ and low‐income groups within a city (Morrison et al, 2022).…”
Section: Spotlight On Social‐ecological Interactionsmentioning
confidence: 99%
“…Microplastics have been reported in human lung tissue (Amato-Lourenco et al, 2021), stool and colectomy samples (Schwabl et al, 2019;Ibrahim et al, 2021), blood (Leslie et al, 2022), and placentas (Ragusa et al, 2021). Plastics impact humans health across levels of biological organization (Morrison et al, 2022), including molecular and cellular processes (Banerjee and Shelver, 2021), tissue and organ systems (Wright and Kelly, 2017), and physiological responses (Karbalaei et al, 2018). Studies characterizing plastics' impact on human health are preliminary and primarily rely on laboratory experiments that simplify real-world exposures (WHO, 2022).…”
Section: The Societal Burden Of Plastic Pollution: Human Health and E...mentioning
confidence: 99%